2002
DOI: 10.1046/j.1460-9568.2002.02254.x
|View full text |Cite
|
Sign up to set email alerts
|

5,7‐dihydroxytryptamine lesions enhance and serotonergic grafts normalize the evoked overflow of acetylcholine in rat hippocampal slices

Abstract: Adult rats were subjected to intracerebroventricular injections of 5,7-dihydroxytryptamine (5,7-DHT; 150 micro g) and, 15 days later, to intrahippocampal grafts of fetal raphe cell suspensions. About 11 months later, we assessed baseline and electrically evoked release of tritium ([3H]) in hippocampal slices, preloaded with tritiated ([3H])choline or [3H]serotonin (5-HT), in the presence or absence of the 5-HT1B receptor agonist CP-93,129 and the 5-HT receptor antagonist methiothepine. HPLC determinations of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 49 publications
1
4
0
Order By: Relevance
“…Rather than blockade of hippocampal 5-HT 1A sites, S15535 and WAY100,635 may, in fact, enhance hippocampal ACh release by blocking tonically active, inhibitory 5-HT 1A sites on cholinergic cell bodies. This would be consistent with findings that lesions of serotonergic neurons increase extracellular levels of ACh in the DH (Steckler and Sahgal, 1995;Birthelmer et al, 2002).…”
Section: Discussionsupporting
confidence: 92%
“…Rather than blockade of hippocampal 5-HT 1A sites, S15535 and WAY100,635 may, in fact, enhance hippocampal ACh release by blocking tonically active, inhibitory 5-HT 1A sites on cholinergic cell bodies. This would be consistent with findings that lesions of serotonergic neurons increase extracellular levels of ACh in the DH (Steckler and Sahgal, 1995;Birthelmer et al, 2002).…”
Section: Discussionsupporting
confidence: 92%
“…Recent studies on hippocampal slices from rats whose serotoninergic neurons were lesioned by intracerebroventricular injection of 5,7-DHT confirmed the data of Vizi et al (1981) in that increased ACh release was found (Birthelmer et al, 2002(Birthelmer et al, , 2003a. This could be ascribed to the attenuated activation of the inhibitory presynaptic 5-HT heteroreceptors on cholinergic projection terminals in the hippocampus.…”
Section: A General Aspectsmentioning
confidence: 70%
“…Interestingly, we could also establish that following serotonergic denervation of the hippocampus (by 5,7-DHT lesions), the electrically evoked release of acetylcholine was facilitated in hippocampal slices. Even more interesting was the observation that this facilitation was counterbalanced by intrahippocampal grafts rich in serotonergic neurons [18]. These results suggest that the reduction of the serotonergic tone in the hippocampus may compensate for some dysfunctions subsequent to a loss of cholinergic hippocampal inputs.…”
Section: Combined Cholinergic and Serotonergic Lesionsmentioning
confidence: 95%
“…Under the condition of a systemic activation, this release can be facilitated via the activation of 5-HT 1A as well as 5-HT 3 receptors, or inhibited via the activation of 5-HT 1B (5-HT 1D in the guinea-pig) and 5-HT 4 receptors [19,43,73,104]. There is also evidence that a serotonergic denervation of the hippocampus is able to facilitate the evoked release of acetylcholine in hippocampal slices [18]. In the cortex, the release of acetylcholine may be locally controlled by 5-HT 1B and 5-HT 3 inhibitory receptors [42,123], whereas systemic activation of 5-HT 1A and 5-HT 4 receptors induces facilitatory effects [5].…”
Section: Introductionmentioning
confidence: 99%